2013
DOI: 10.1016/j.molstruc.2013.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Glycolaldehyde dimer in the stable crystal phase has axial OH groups: Raman, infrared and X-ray data analysis

Abstract: Mohaček-Grošev, V., Prugovečki, B., , ''Glycolaldehyde dimer in the stable crystal phase has axial OH groups: Raman, infrared and X-ray data analysis '', Journal of Molecular Structure, Vol. 1047, pp. 209-215. Glycolaldehyde dimer in the stable crystal phase has axial OH groups:Raman, infrared and X-ray data analysisGraphical abstract AbstractAlthough a small molecule and a simple 1,4-dioxane derivative, 2,5-dihydroxy-1,4-dioxane or glycolaldehyde dimer has a crystal structure that has eluded researchers s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…The dimer could be as ix-membered (1,4-dioxane-2,5-diol) or af ive-membered ring [2-(hydroxymethyl)-1,3-dioxan-4-ol],a lthough it is knownt hat the compound is ad ioxane. [11,14] Our experimental and computational resultsb ased on Ramans pectroscopy and an exhaustive ab initio conformational search reveal the existence of enediol species (in their enediolatef orms)i nb asic environment, and they correctm uch of the literature that provides erroneous results when an enediol structure is assigned in neutral medium.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…The dimer could be as ix-membered (1,4-dioxane-2,5-diol) or af ive-membered ring [2-(hydroxymethyl)-1,3-dioxan-4-ol],a lthough it is knownt hat the compound is ad ioxane. [11,14] Our experimental and computational resultsb ased on Ramans pectroscopy and an exhaustive ab initio conformational search reveal the existence of enediol species (in their enediolatef orms)i nb asic environment, and they correctm uch of the literature that provides erroneous results when an enediol structure is assigned in neutral medium.…”
Section: Introductionsupporting
confidence: 59%
“…With regardt ot he solidp hase, Mohaček-Grošev et al [11] reported on the stable crystal structure of the glycolaldehyde dimer characterizedb yX -ray powder diffractiona tr oom temperature. The glycolaldehyde dimer molecules are trans-isomers with the electronegative hydroxyl groupsi naxial dispositions.…”
Section: Introductionmentioning
confidence: 99%
“…This structure is closely related to that of glycolaldehyde dimer as inferred from X-ray studies too (Mohaček-Grošek et al 2013). As mentioned, the first chiral sugar, glyceraldehyde, may form a stable dimer in the solid state.…”
supporting
confidence: 69%
“…The asymmetric unit contains two halves of the symmetrically independent glycolaldehyde dimer molecules which lie on inversion centers. Analysis of the bond lengths revealed that the C−O bonds in one symmetrically independent glycolaldehyde dimer molecule in the β-form is lengthened in comparison to the previously reported α-glycolaldehide dimer [5] (Supporting Information, Table S1).…”
Section: X-ray Crystallographymentioning
confidence: 68%
“…[3] Glycolaldehyde, CHOCHOH, is at room temperature a polycrystalline solid, existing in the form of 2,5-dihydroxy-1,4-dioxane or glycolaldehyde dimer, whose αand βpolymorphs were first distinguished by Kobayashi et al [4] The conformation of hydroxyl groups was assumed equatorial in the α-phase and axial in the β-phase. Recently, the crystal structure of the α-polymorph was solved by Mohaček-Grošev et al [5] and it was found that molecules crystallize with axially placed OH groups. On cooling, αphase transforms into the third γ-phase below 80 K. [6] Dissolving of glycolaldehyde is a complex, time dependent process.…”
Section: Introductionmentioning
confidence: 99%